Improving Students Ability in Pronunciation Through Reading Aloud for the 8th Grade of SMPN 2 Bukittinggi - Mardiah, Ainun; Safitri, Loli; Eliza, Eliza; Syahrul , Syahrul (Pusdikra Publishing, 2024)
This research aims to describe the improvement in students' pronunciation through reading aloud. Based on the problem found by the reseracher most of the students have difficulty in pronouncing some words in English such as minimal pairs. Many students did not achieve the completenes criteria (KKM) namely 70, meanwhile the average students score was only 55,15. This research used classroom action research (CAR) that consisted of 2 cycles. The subjects of this research were grade 8 of SMPN 2 Bukittinggi consisted 32 students.The instruments used were oral tests and observations sheet. In analyzing the data, this research used quantitative and qualitative data. Quantitatively, data was obtained from student scores in pronunciation test. Qualitative data was obtained from the results of observation sheet. The results obtained in the first test cycle showed an average student score of 61,68, with a percentage of succsess only 37,5% or 12 out of 32 students who passed the KKM, meanwhile in the second cycle the percentage of success in improving students' pronunciation was 81.25% with an average score of 76,15 where there was 26 students who passed the KKM. The increased from cycle 1 to cycle 2 was 23,45%. In observations sheet, researcher found that used reading aloud can improve students' pronunciation abilities, seen from accuracy and fluency aspect. this was strengthened by observations that showed the classroom situation is also more conducive and students more interested and enthusiastic during the teaching and learning process. In other words, it can be concluded that reading aloud can improve students' pronunciation abilities.